Review on materials & methods to produce controlled release coated urea fertilizer - Azeem, B. (Elsevier, 2014)
With the exponential growth of the global population, the agricultural sector is bound to use ever larger quantities of fertilizers to augment the food supply, which consequently increases food production costs. Urea, when applied to crops is vulnerable to losses from volatilization and leaching. Current methods also reduce nitrogen use efficiency (NUE) by plants which limits crop yields and, moreover, contributes towards environmental pollution in terms of hazardous gaseous emissions and water eutrophication. An approach that offsets this pollution while also enhancing NUE is the use of controlled release urea (CRU) for which several methods and materials have been reported. The physical intromission of urea granules in an appropriate coating material is one such technique that produces controlled release coated urea (CRCU). The development of CRCU is a green technology that not only reduces nitrogen loss caused by volatilization and leaching, but also alters the kinetics of nitrogen release, which, in turn, provides nutrients to plants at a pace that is more compatible with their metabolic needs. This review covers the research quantum regarding the physical coating of original urea granules. Special emphasis is placed on the latest coating methods as well as release experiments and mechanisms with an integrated critical analyses followed by suggestions for future research. Â© 2014 Elsevier B.V.